Potencialidades do uso de software em sequência didática no ensino de conceitos de oxirredução - Silva, Vanessa Masteguim da (2017)
Science students, in particular Chemistry, must understand science in its entirety, having to learn notions of what occurs in the submicroscopic environment of mat-ter, which is reflected in the macroscopic environment, as well as the aspects of language that mediate chemical concepts. In this work we address the following problems: what are the didactic potentialities of the use of an educational soft-ware to learn the concept of oxidation in metals by high school students. This qualitative research was carried out with seven students of the third year of High School of a State College located in the municipality of Tamboara / PR, from April to May 2016, and had as main objective to analyze a methodological proposal regarding the Experimentation linked to information and communication technol-ogy (ICT), about the concept of oxidation in metals, which involved the use of appropriate software. The results were analyzed based on James Wertsch's The-ory of Mediated Action and after analyzing them, we found several levels of Do-minion (weak, moderate and strong) as well as several levels of appropriation (weak, moderate and strong). According to Wertsch (1999), when dominating or appropriating, the subject obtains a meaning from the concepts learned, in this case, oxidation processes. This fact, reveals that the process which was medi-ated during the teaching, exceeded the information and enabled the student to obtain knowledge of all the oxidative processes.